Kajian Kerusakan Lingkungan Sungai Praigaga Akibat Kegiatan Pertambangan Timah - Balla Nggiku , Umbu Amar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The change in the profile of the Praigaga River trough around the tin mining of Praimadita Village due to mining is done by three points: the upstream of the river has a width of 6 m and a depth of 120 cm forming the letter